Struggling Access to Justice through Mediation in Bangladesh: Headway Lessons from Australia - Chowdhury, Jamila A; Siddiqui, Mehnaz (UI Scholars Hub, 2025)
Enormous case backlog and protracted delays in courts are hindering access to justice in Bangladesh. Consequently, an initiative to provide quick and low-cost consensual justice through mediation was first initiated in the family courts of Bangladesh in the year 2000. However, although after an initial success, the system has been struggling over the decades. While contemporary research has identified various constraints causing such meager disposal of cases in family courts, using expert interviews of family court judges and relevant literature review on Australian family courts, this Chapter reiterates such constraints to generate relevant headway lessons from Australia that has excelled the practice of family mediation and becomes one of the world frontrunners in this field. Hence, the outcome of this study will assist policymakers in adopting relevant policies to redress case backlog and enhance gender justice through mediation in Bangladesh.